SANKSI GEREJA DAN IMPLIKASINYA DALAM GEREJA KEUSKUPAN AMBOINA MENURUT KITAB HUKUM KANONIK 1983 - Ngutra, Seno (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2016)
Sanctions in the Church is not a punishment, but a process of learning of how to obey to the law of the Church, and with a greatfull heart taking responsibility to what we have done as a mistake that have broken the commitment of all members of community. Therefore, the sanction of the Church must be understood as a grace to all the faithfull who wants to reconcile with the Church as a mother in faith and moral. As a mother, the Church must guide her chidren to grow up in their life to be the good sons and daughters of one God as the Father. This arcticel will be a guideline for every faithful to understand the meaningful behind the sanctions in the Church.